2015
DOI: 10.1074/jbc.m114.609685
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF) Receptor-associated Factor (TRAF)-interacting Protein (TRIP) Negatively Regulates the TRAF2 Ubiquitin-dependent Pathway by Suppressing the TRAF2-Sphingosine 1-Phosphate (S1P) Interaction

Abstract: Background: TNF receptor-associated factor 2 (TRAF2) is a key adaptor molecule in the TNF receptor (TNFR) signaling pathway. Results: TRAF-interacting protein (TRIP) inhibits Lys63 -linked TRAF2 ubiquitination by blocking the binding of the cofactor sphingosine 1-phosphate (S1P) to the TRAF2 RING domain. Conclusion: TRIP negatively regulates the TRAF2 ubiquitin-dependent pathway by modulating the TRAF2-S1P interaction. Significance: TRIP is an important cellular regulator of the TNFR-mediated inflammatory resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 48 publications
4
65
0
1
Order By: Relevance
“…As SphK1 also physically interacts with FLNA (9), FLNA may act as a scaffold to allow localized production of S1P, which in turn binds and activates TRAF2, leading to NF-B signaling. Recent studies have shown that TRAF-interacting protein (TRIP), a known cellular binding partner of TRAF2 (27), inhibits TNF-induced NF-B activation by inhibiting the binding of S1P to TRAF2 and thus suppressing its E3 ubiquitin ligase activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…As SphK1 also physically interacts with FLNA (9), FLNA may act as a scaffold to allow localized production of S1P, which in turn binds and activates TRAF2, leading to NF-B signaling. Recent studies have shown that TRAF-interacting protein (TRIP), a known cellular binding partner of TRAF2 (27), inhibits TNF-induced NF-B activation by inhibiting the binding of S1P to TRAF2 and thus suppressing its E3 ubiquitin ligase activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…The GST-fused (GST-TRAF6), red fluorescent protein-fused (RFP-TRAF6), and Xp-tagged TRAF6 (Xp-TRAF6) and the FLAG-tagged TRAF6 deletion mutants were constructed by PCR amplification and insertion in pEBG (39), pDsRed-Monomer-N1 (BD Biosciences Clontech, Mountain View, CA), pcDNA3.1-His (Invitrogen), pFLAG-CMV2 (Sigma-Aldrich), and pMX-puro-FLAG (37), respectively. The FLAG-tagged TRAF members were described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…To generate T6BS-deficient mutants, all consensus Glu residues in the T6BSs were mutated to Ala by PCR amplification as previously described (39), and the mutated fragments were subcloned into pFLAG-CMV1 (FLAG-RANK-AAA) or pEBG (GST-RANK cyto -AAA). The retroviral expression plasmids for the chimeric receptor of human CD40 and murine RANK cyto (hCD40/mRK) and its T6BS-deficient mutant (hCD40/mRK-AAA) were described previously (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations